Perceptions of medical and public health professionals on climate change and emerging health challenges in Pakistan: a multi-scale approach - Hira Tariq; Shahmeen Nazar; Umm-e-Rabab; Sameena Ourangzaib (BMC Medical Education)
Abstract Background and objectives Climate change is a significant global health threat, disproportionately impacting low- and middle-income countries. Urban centres like Karachi, Pakistan, face rising incidences of vector-borne and waterborne diseases because of changing climate (CC). This study aimed to explore the perceptions of healthcare professionals regarding climate change, its health impacts, and their role in addressing these challenges. Methods A qualitative study was conducted using nine focus group discussions with 46 healthcare professionals, including doctors, nurses, and public health experts from three major hospitals and two postgraduate institutions in Karachi. Participants were recruited through snowball sampling, and data were collected using semi-structured interviews. Thematic analysis was conducted to identify both manifest and latent themes in the data. Results The analysis revealed seven major themes: awareness of climate change, health impacts, economic and social consequences, environmental and natural disasters, the role of healthcare professionals, mitigation strategies, and policy challenges. Participants demonstrated varied levels of awareness, influenced by their educational background and professional specialization, with public health professionals exhibiting a broader understanding compared to other healthcare workers. Key concerns included the rise of infectious diseases, food insecurity, and urban resource strain. Participants identified barriers such as inadequate training, limited resources, and weak policy enforcement that hinder their ability to address climate impacts effectively. Conclusions Healthcare professionals in Karachi play a critical role in mitigating climate-related health impacts. Enhanced education, integration of climate change into medical curricula, and interdisciplinary collaboration are essential. Strengthened policies and systemic investments are needed to empower healthcare workers as leaders in climate adaptation and mitigation efforts.